2014
DOI: 10.1088/0031-9155/59/7/1831
|View full text |Cite
|
Sign up to set email alerts
|

The contribution from transit dose for192Ir HDR brachytherapy treatments

Abstract: Brachytherapy treatment planning systems that use model-based dose calculation algorithms employ a more accurate approach that replaces the TG43-U1 water dose formalism and adopt the TG-186 recommendations regarding composition and geometry of patients and other relevant effects. However, no recommendations were provided on the transit dose due to the source traveling inside the patient. This study describes a methodology to calculate the transit dose using information from the treatment planning system (TPS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The transit dose component of a brachytherapy source movement from the safe to the dwell positions, between the dwell positions, and when returning to the safe has been studied previously, [1][2][3][4][5][6][7] reporting differences up to a factor of 10 for the source speed for the same afterloader. 8 The effect of these differences on the transit dose component for clinical brachytherapy treatments performed with a HDR 192 Ir source was evaluated recently. 8 The study demonstrated potentially significant dose variations depending on the speed profile.…”
Section: Introductionmentioning
confidence: 99%
“…The transit dose component of a brachytherapy source movement from the safe to the dwell positions, between the dwell positions, and when returning to the safe has been studied previously, [1][2][3][4][5][6][7] reporting differences up to a factor of 10 for the source speed for the same afterloader. 8 The effect of these differences on the transit dose component for clinical brachytherapy treatments performed with a HDR 192 Ir source was evaluated recently. 8 The study demonstrated potentially significant dose variations depending on the speed profile.…”
Section: Introductionmentioning
confidence: 99%
“…HDR source transit dose has long been recognized and explored by many researchers using various methods [26,3842]. Among them, Fonseca, et al have extensively evaluated the transit dose of the 192 Ir HDR afterloader, with respect to the source speed profiles, for a more realistic dose correction [3840]. For the skin applicator however only one dwell position is used and the absolute transit dose contribution is a function of source activity only.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the accuracy of dwell-times it is important to take into account that most manufacturers include the transit time in the dwell time of the next dwell position, except for the first dwell-position [23,24]. Note that the clinical effects of the transit dose can be substantial (see appendix 2) [25].…”
Section: Accuracy Of Dwell-timesmentioning
confidence: 99%
“…The transit dose component increases with increasing number of catheters, reducing the total dwell time per catheter or increasing the number of dwell positions with low dwell times. This contribution may become significant (>5%) if it is not corrected for appropriately [25]. Transit dose correction based on average source speed fails to accurately correct the dose, indicating that accurate measurement of the source acceleration and speed profile should be considered [58].…”
Section: Testmentioning
confidence: 99%